Tele-Assessment of Functional Capacity through the Six-Minute Walk Test in Patients with Diabetes Mellitus Type 2: Validity and Reliability of Repeated Measurements - Pepera, Garyfallia; Karanasiou, Evmorfia; Blioumpa, Christina; Antoniou, Varsamo; Kalatzis, Konstantinos; Lanaras, Leonidas; Batalik, Ladislav (Sensors (Basel, Switzerland), 2023)
A tele-assessed 6MWT (TL 6MWT) could be an alternative method of evaluating functional capacity in patients with diabetes mellitus type 2 (DM2). This study aimed to assess the validity and reliability of a TL 6MWT. The functional capacity of 28 patients with DM2 (75% men) aged 61 ± 13 years was evaluated twice via an indoor, center-based 6MWT (CB 6MWT) and twice outside each patient's home via a web-based platform TL 6MWT. The study showed a high statistically significant correlation between the CB and TL 6MWT (Pearson's r = 0.76, p < 0.001). Reliability testing showed no statistically significant differences in the distance covered (CB1: 492 ± 84 m and CB2: 506 ± 86 m versus TL1: 534 ± 87 m and TL2: 542 ± 93 m, respectively) and in the best distance of the TL 6MWT (545 ± 93 m) compared to the best CB distance (521 ± 83 m). Strong internal reliability for both the CB (intraclass correlation coefficient (ICC) = 0.93) and the TL 6MWT (ICC = 0.98) was found. The results indicate that a TL 6MWT performed outdoors can be a highly valid and reliable tool to assess functional capacity in patients with DM2. No learning effect between the TL and CB assessment was found, minimizing the need for repetition.
Keywords: diabetes mellitus; six-minute walk test; Male; Walking; Walk Test; test chůzí; Diabetes Mellitus, Type 2; mužské pohlaví; telehealth assessment; reprodukovatelnost výsledků; diabetes mellitus 2. typu; Reproducibility of Results; zátěžový test; chůze; Exercise Test; lidé; ženské pohlaví; Humans; tele-assessment; remote assessment; Female; functional capacity